2019
DOI: 10.1007/s11357-019-00133-8
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal cord microglia exhibited increased activation in aging dogs compared with young adult dogs

Abstract: Altered microglia function contributes to loss of CNS homeostasis during aging in the brain. Few studies have evaluated age-related alterations in spinal cord microglia. We previously demonstrated that lumbar spinal cord microglial expression of inducible nitric oxide synthase (iNOS) was equivalent between aging, neurologically normal dogs and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…Our finding that microglia tiling was disrupted with age primarily in the ventral horn led us to suspect that these microglia were migrating to a specific subregion of the ventral horn, as they respond to some type of stimulus. Our analysis of microglia‐neuronal interactions revealed an obvious association between aged microglia lacking a ramified morphology and motor neurons, which has been alluded to previously in aged canines (Toedebusch et al, 2020). Importantly, recent evidence has also linked microglia accumulation in the ventral horn to the degeneration of motor neurons in aged humans (Buchman et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our finding that microglia tiling was disrupted with age primarily in the ventral horn led us to suspect that these microglia were migrating to a specific subregion of the ventral horn, as they respond to some type of stimulus. Our analysis of microglia‐neuronal interactions revealed an obvious association between aged microglia lacking a ramified morphology and motor neurons, which has been alluded to previously in aged canines (Toedebusch et al, 2020). Importantly, recent evidence has also linked microglia accumulation in the ventral horn to the degeneration of motor neurons in aged humans (Buchman et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Contact was defined as direct apposition or overlap of the GFP and NeuN signal regardless of the location of this contact on either cell. We focused on the lumbar spinal cord region because motor neurons in this region display increased susceptibility to age‐related degeneration as compared to more rostrally located regions (Mayhew et al, 2020; Toedebusch et al, 2020). We found that individual neurons in the DH, IG, and VH were contacted by a similar number of microglia in young adult mice (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Morphometric analysis of intratumoral Iba-1+ cells revealed that normal canine brain demonstrated the homogeneous distribution of Iba-1+ cells with a small cell body and several branched processes, consistent with a ramified morphology ( Figure 2A ). 27 Conversely, GAM morphology across tumor grades reflected a larger cellular population lacking the typical ramified morphology ( Figure 2 ). Compared to normal cortical microglia, the total GAM area was increased in grade III astrocytomas (551 ± 103 vs 279 ± 25; P < .05; Figure 2A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…The existing literature, as well as our study, support the presence of both para-inflammatory state and demyelination in the aging spinal cord. Moreover, a recent study by Toedebusch et al (2019) reports microglia polarization toward a pro-inflammatory phenotype preferentially in the lumbar spinal cord of aging dogs. The reported "primed" state of the microglia corresponds to microglia activation without pronounced cytokine release, similar to what we observed in this study.…”
Section: Discussionmentioning
confidence: 96%